Invasive Microascus trigonosporus Species Complex Pulmonary Infection in a Lung Transplant Recipient - Kelly E. Schoeppler; Martin R. Zamora; Noelle M. Northcutt; Gerard R. Barber; Gayle O’Malley-Schroeder; Dennis M. Lyu (Case Reports in Transplantation)
Because of the high incidence of morbidity and mortality associated with invasive fungal infections, antifungal prophylaxis is often used in solid organ transplant recipients. However, this prophylaxis is not universally effective and may contribute to the selection of emerging, resistant pathogens. Here we present a rare case of invasive infection caused by Microascus trigonosporus species complex in a human, which developed during voriconazole prophylaxis in a lung transplant recipient. Nebulized liposomal amphotericin B was used in addition to systemic therapy in order to optimize antifungal drug exposure; this regimen appeared to reduce the patient’s fungal burden. Despite this apparent improvement, the patient’s pulmonary status progressively declined in the setting of multiple comorbidities, ultimately leading to respiratory failure and death.